MODELING OF THE CENTER OF RADIOACTIVE CONTAMINATION IN THE EVENT OF AN ATOMIC REACTOR ACCIDENT - Канунніков, Б. Т.; Лук’янников, В. А.; Применко, В. І. (Proceedings of National Aviation University (archive), 2021)
Models of formation of the center of radioactive contamination are considered. The optimal geometric shape of the radiation cell is selected. A method for calculating its depth is proposed. The characteristics of radiation contamination as a function of recoil and time are determined.